Supporting the Tourism Industry in the Context of the Coronavirus Pandemic and Economic Crisis: Social Tourism and Public-Private Partnership - SHUBTSOVA, Lyudmila Vladimirovna; KOSTROMINA, Elena Alexandrovna; CHELYAPINA, Olga Ivanovna; GRIGORIEVA, Natalia Anatolyevna; TRIFONOV, Pavel V. (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020DO - 10.14505/jemt.v11.6(46).13, 2020)
The present article explores the possibilities of restoring the tourism industry in the Russian Federation by attracting investment and public-private partnership. The purpose of the study is to analyze the possibilities of restoring the Russian tourism industry, taking into account the losses incurred due to the COVID-19 pandemic, and to determine the main areas of state support. The article provides an analysis of statistical information showing the calculated amount of damage to the tourism industry from the spread of coronavirus infection, and possible negative consequences in the future, as well as data from an expert sociological survey. The authors analyze the measures and the need for state support for the industry that is in an ongoing state of economic crisis and note the problems of tourism development in Russia and several European countries that resulted from the spread of coronavirus infection. The authors consider possibilities and prospects of restoring the tourism industry in the future, describe measures to support the tourism industry planned by the Russian government, as well as anti-crisis programs undertaken in several European countries that are designed to help the tourism industry survive during the crisis. It is shown that support measures undertaken in Russia are incomparable with the help provided to the tourism industry by the governments of several European countries. The authors question the effectiveness of these measures as well as consider possible changes in the business model of the tourism industry and the opportunities to increase the role of public-private partnership projects. The results and suggestions proposed by the authors will be of interest to both the tourism business practitioners, investors in the tourism industry, representatives of relevant government agencies, and researchers studying issues of state regulation of the tourist services market.